2006
DOI: 10.1002/bdra.20325
|View full text |Cite
|
Sign up to set email alerts
|

Role of geographic information systems in birth defects surveillance and research

Abstract: We recommend a broad and systematic use of GIS in birth defects spatial surveillance and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…The biomedical and public health literature on geographic information systems (GIS) and spatio-temporal analyses features a large number of research papers mentioning or addressing location privacy, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
“…The biomedical and public health literature on geographic information systems (GIS) and spatio-temporal analyses features a large number of research papers mentioning or addressing location privacy, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
“…Recent MACDP analyses found that 20% of pregnant women in Atlanta changed residences between the dates of conception and delivery (Siffel et al, 2006). Location misclassification errors also can occur because the geocode corresponding to maternal residence is used as an overall proxy for spatial location.…”
Section: Discussionmentioning
confidence: 99%
“…These data have also been used to evaluate seasonality in birth defects prevalence (Siffel et al, 2005) and to monitor temporal trends in NTDs and other birth defects in relation to folic acid fortification (Honein et al, 2001;Canfield et al, 2005;Williams et al, 2005;Dolk, 1999). Use of birth defects surveillance data for monitoring spatial patterns in the occurrence of birth defects (e.g., spatial clusters and differential ascertainment patterns) has been more limited (Forand et al, 2002;Babcock et al, 2005;Siffel et al, 2006). However, as birth defects surveillance programs become better able to incorporate geocoded records in their databases, a question arises regarding the availability of practical methods to expand monitoring to utilize the spatial dimension of the data.…”
Section: Introductionmentioning
confidence: 98%
“…Several reported the use of private firms to geocode their data without providing the level of methodological detail presented here. [33][34][35][36] Whether geocoding is done in-house or by a commercial firm, reporting the detailed methods and geocoding results are important for assessing validity as accuracy and error varies using either method. 11,37 The description of the phases, processes, and decisions involved in retrospectively creating a GIS in the JHS provides a basis for future studies to include in study protocols.…”
Section: Discussionmentioning
confidence: 99%